Some remarks regarding the procedure of the appointment of the secretary general of the United Nations - Novaković Marko (Anali Pravnog Fakulteta u Beogradu)
Appointing Secretary-General is a process that has always been enshrined in secrecy. In 2016, due to reforms in the appointment process instigated by the president of the Security Council Mogens Lykketoft, more inclusion and transparency have been achieved, with the non-state actors being much more involved in the process. In the procedure itself, first five straw polls suggested that Antonio Guterres will be the new Secretary-General and this proved to be truth. Will this more transparent system result in appointment of the most appropriate candidate is the question that will be partially answered. In this article we will try to assess how much is done towards this goal and what still needs to be done. Moreover, we will investigate some aspects of the appointment procedure and pressing issues that Antonio Guterres will have to face.